Emily Bronte - Pykett, Lyn (Rowman & Littlefield Publishers, 1989)
Emily Bront_'s writings explore, expand, and transgress limited nineteenth-century ideas of the nature of the female lot and of women's creativity. This study offers an extensive rereading of the poems which focuses on Emily Bront_'s problematic relationship to the Romantic tradition in which they were produced, and to the critical tradition in which they have been reproduced. Using recent feminist work on gender and genre Lyn Pykett throws fresh light on the complexities of Wuthering Heights, and suggests that much of this novel's distinctiveness may be attributed to the particular ways in which it both combines and explores Female Gothic and the emerging realist domestic novel, a genre also widely used and read by women. Contents: Emily Bront_: A Life Hidden from History; The Writings of Ellis Bell; 'Not at all like the poetry women generally write' Emily Bront_ and the Problem of the Woman Poet; Death Dreams and Prison Songs; Gender and Genre in^R Wuthering Heights; Changing the Names: The Two Catherines; Nelly Dean: Memoirs of a Survivor; The Male Part of the Poem; Reading Women's Writing: Emily Bront_ and the Critics